LOW WATER CEMENTS BASED ON ACTIVE MINERAL ADDITIVES OF VARIOUS ORIGINS - R. G. Bisultanov; C.-A. Y. Murtazaev; Salamanova M. Sh. (Вестник Дагестанского государственного технического университета: Технические науки)
We consider the problems associated with the development of high-efficient binders. It was found that the mortars and concretes important indicator is the ratio of binding properties of cements with a so-called ”specific consumption of aggregates. ” It was found that the activity of Portland cement in the past decade has increased slightly and is 50-55 MPa; physical and technical characteristics of high-quality graded fine and coarse aggregates remained unchanged. It substantiates the relevance of the development of new types of cements for high-strength and high-quality concrete with active mineral additives and an effective superplasticizers. It is proved that the use of the obtained cements of low water through the use of active mineral additives of different origin, allows to obtain high-quality concrete with strength class from B60 to B100, reduce the need for water-mortar and concrete mixtures of 25-30% for equal mobility.